Order and structure in syntax I Word order and syntactic structure - Sheehan, Michelle; R. Bailey, Laura (Open Generative Syntax, 2017)
This book reconsiders the role of order and structure in syntax, focusing on fundamental issues such as word order and grammatical functions. The first group of papers in the collection asks what word order can tell us about syntactic structure, using evidence from V2, object shift, word order gaps and different kinds of movement. The second group of papers all address the issue of subjecthood in some way, and examine how certain subject properties vary across languages: expression of subjects, expletive subjects, quirky and locative subjects. All of the papers address in some way the tension between modelling what can vary across languages whilst improving our understanding of what might be universal to human language.